Penerapan analisis SOAR dalam strategi pengembangan Hotel di Kota Bandung - Muhamad Ardi Nupi Hasyim (STIE Bangkinang Publishing, 2023)
This study aims to determine the right strategy for hotel business development and also the strategic environment owned and faced by Hotel in Bandung City. This research is a qualitative type with a descriptive approach. The data collection methods used are documentation, observation and interviews. The analytical method used in this research is the 5-I approach (Initiate, Inquire, Imagine, Innovate, Implement) and SOAR analysis (Strengths, Opportunities, Aspirations, Results). The results of this research show that the strategies that can be carried out by Hotel in Bandung City are Market penetration strategies by doing better marketing starting from marketing through social media, E-commerce, endorsements from people who have many followers and creating interesting content. which can attract many customers and also strategy product development can be done by packaging and programming, so how to package a product to make it attractive and varied.